A highly sensitive electrochemical sensor containing nitrogen-doped ordered mesoporous carbon (NOMC) for voltammetric determination of l-tryptophan. (1st October 2020) - Zhang, Yi; Waterhouse, Geoffrey I.N.; Xiang, Zhi-peng; Che, Jing; Chen, Chong; Sun, Weizheng
Highlights: A NOMC/Nafion/GCE electrochemical sensor for l -tryptophan analysis was fabricated. The sensor had high sensitivity and high selectivity for Trp. Trp oxidation on the NOMC/Nafion/GCE sensor was a two-electron/two-proton process. The sensor allowed analysis of Trp in amino acid mixtures or protein hydrolysates. Abstract: This study developed a novel electrochemical sensor containing nitrogen-doped ordered mesoporous carbon (NOMC) for the sensitive and selective quantification of l -tryptophan (Trp). The electro-oxidation mechanism of Trp on the NOMC/Nafion/glass carbon electrode (GCE) was first investigated, and was found to follow a two-electron/two-proton transfer mechanism. Subsequently, the analytical operation conditions were optimized. Under the optimum testing conditions, the oxidation current was found to increase linearly with Trp concentration in the ranges 0.5–70.0 μM and 70.0–200.0 μM (different slopes in each range), with the limit of detection determined to be 35.0 nM (S/N = 3). In addition, the sensor was highly selective for Trp and showed good repeatability and long-term stability. Studies of Trp in real world systems, such as an 18 amino acid mixture and an enzymatic protein hydrolysate, showed excellent recoveries (99.30–103.60%). Results suggest that NOMC/Nafion/GCE sensor has excellent performance characteristics for routine Trp analysis.